Sustainability assessment of corn production systems in the Yucatan Peninsula - Uzcanga-Pérez, Nelda Guadalupe; Cano-González, Alejandro de Jesús; Chanatásig-Vaca, Cristina Isabel (Ecosistemas y Recursos Agropecuarios, 2022)
The objective of this research was to evaluate the sustainability of the resource management systems used for the production of rainfed corn in the Yucatan Peninsula. The Evaluation Framework of Management Systems with Sustainability Indicators (MESMIS) (Spanish acronym) used in three systems: milpa, conventional and mechanized. Criteria and indicators defined in line with the sustainability attributes: productivity, stability, resilience and reliability, adaptability, equity and Self-reliance and the critical points identified. The evaluation was carried out through the definition, calculation and monitoring of nine indicators: yield, cost-benefit ratio, index of sustainable agricultural aptitude, index of appropriation of agricultural technology, index of productive capacity, level of food security with respect to the corn, land distribution, Gini coefficient, and external dependence on inputs. The information obtained from 733 questionnaires, participatory workshops and documentary research, which integrated with multi-criteria techniques to make value judgments on the management systems. The alternative system was more sustainable in most attributes with the exception of Self-reliance due to the government support it received. The milpa was more sustainable than the conventional system, due to the distribution of the land and was even more sustainable than the mechanized system due to its low external dependence on inputs. Finally, the conventional system was the least sustainable than the milpa and mechanized system.